Gasification conversion and char reactivity of rubber seed shell and high density polyethylene mixtures using steam Co-Gasification process - Chin, B.L.F. (Italian Association of Chemical Engineering - AIDIC, 2014)
Due to the recent surge of global energy demand and the fear of climate change, an extensive attention from worldwide in seeking for cleaner alternative means of renewable energy and this has been a topic of interest widely. With the abundance supply of biomass and plastic waste generated annually and finding an effective method in utilizing these wastes, leads to a notion of using these wastes in the co-gasification process. Although there are studies on co-gasification of biomass and waste mixtures, limited studies focused on the understanding of the char reactivity and gasification conversion of this mixture. Hence, an experimental study on steam co-gasification of rubber seed shell and high density polyethylene mixtures in argon atmosphere is carried out using thermogravimetric (TGA) approach under non-isothermal condition. This work presents the surface physical morphology of rubber seed shell (RSS), high density polyethylene (HDPE), and its mixtures. Furthermore, the char conversion and char reactivity of RSS, HDPE, and their mixtures at different proportions are investigated in both pyrolysis and gasification process. The argon gas is supplied at a flowrate of 100 mL min-1 and the steam is generated from superheater at 383 K whilst injected at flowrate of 3000 Î¼L h-1 into the TGA system. Copyright Â© 2014, AIDIC Servizi S.r.l.